Effectiveness of Mystery Card Media of DentalHealth Knowledge Among Preschool Children inSurabaya - Helly Lailiyah Mufarikhah Mufarikhah; Isnanto; Ratih Larasati; Husnul Wafa (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2025)
Dental health problems remain highly prevalent among preschool children, largely due to inadequate knowledge ofproper oral hygiene practices. Preliminary findings at Maryam Islamic Kindergarten, Surabaya, showed that most children exhibitedpoor dental health knowledge and high caries risk, highlighting the need for more engaging and developmentally appropriateeducational media. This study aimed to evaluate the effectiveness of the Mystery Card media, an interactive learning tool integratingprinted cards with technology, in improving dental health knowledge among preschool children. A quasi-experimental pretest–posttest control group design was conducted from December 2024 to March 2025, involving 46 preschool children selected throughsimple random sampling. Participants were divided into intervention and control groups. The intervention group received educationusing Mystery Card media, while the control group received conventional instruction through PowerPoint presentations.Knowledge data were collected using a validated questionnaire and analyzed using the Wilcoxon and Mann-Whitney tests with asignificance level of α = 0.05. The results demonstrated a substantial improvement in the intervention group, where the proportionof children in the “good” knowledge category increased from 0% at pretest to 95.7% at posttest (p = 0.000). The control group showed improvement only to the “adequate” category, with no children reaching the “good” category (p = 0.037). The Mann-Whitney analysis confirmed a significant posttest difference between the two groups (p = 0.000), indicating the superior effectiveness of the Mystery Card media. In conclusion, Mystery Card media significantly enhances dental health knowledge amongpreschool children, outperforming traditional instructional methods. Its interactive features, combining visual and auditory stimuli,create a more engaging learning experience that supports better comprehension and retention. The findings suggest the potential ofMystery Card media as an innovative strategy for early oral health education.